Use and effects of computer assited language learning on (CALL) 11th grade students at Francisco Morazán High School of David, Chiriquí, 2013 - Quintero, Keyla (UDELAS, 2013)
Today, Panama stands at a crossroad. One hundred years have passed since the opening of Panama Canal, and this country must decide in which direction its future lies. Some people believe that it is sufficient for our country to glory in our past, and rest on our laurels.